Theoretical Basis of Leveling Tillage in A Paraplow-Type Slanted-Column Chisel Plow - Begmurodovich, Irgashev Dilmurod (International Journal on Human-Computing Studies, 2025)
This study presents a comprehensive approach to determining the optimal longitudinal spacing between the lower deep-loosening shanks and the upper working tools of two-tier chisel-type plows. By integrating soil deformation modeling, traction resistance optimization, and both analytical and graphical methods, the research highlights the importance of proper spacing in enhancing soil loosening efficiency. The results show that optimizing this spacing improves soil aeration, reduces traction resistance, and minimizes tool wear, while maintaining soil structure. The study provides analytical formulas and practical engineering guidelines that are essential for the design and calibration of plows used in deep tillage. These guidelines ensure the effective improvement of soil properties and promote energy-efficient operation, making the plows more suitable for sustainable agricultural practices.